The impact of globalization, macroeconomic variables, and financial development on economic growth: Evidence from ASEAN countries - Syahda, Putri Eliza; Retnasih, Nora Ria (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
Globalization in the modern world is behind the formation of emerging market countries through the transition in economic growth. ASEAN is considered as the driving force of the world economy, including the emerging market countries that grow within it.  However, economic growth in ASEAN emerging market countries still has to face many challenges. In macro analysis, the parameter of economic growth is GDP. Over time economists have highlighted that there are many other indicators, one of which is globalization, macroeconomic performance and financial development. The aim of this research is to analyze the impact of globalization, inflation, public spending, human capital and financial development on economic growth. This research is relevant because it relates to factors that affect economic growth amid increasingly complex global challenges by providing a comprehensive view of the relationship between variables. This type of quantitative research is based on secondary data. The sampling procedure employed is purposive sampling, which was applied to 5 countries. Data analysis using the PVECM or panel VECM method. The results showed that in the long run globalization, inflation, physical capital, and financial development affect economic growth, but government spending has no effect. While in the short term both lag 1 and 2 all variables affect economic growth. The implication of the study that  government to prioritize the effective allocation of public spending, ensuring that funds are directed toward productive sectors such as infrastructure, education, and health.